Srednja Evropa v literarnovedni razpravi - Zelenka, Miloš (Primerjalna književnost, 2009)
Making Central Europe the subject of literary and culturological interpretation, the study shows that this cultural and geographical area has typically had unstable centres and peripheries with a changeable position, with intermingling nacionalities, cultures and creeds. Its specific mode of communication has brought about untraditional exchanges of literary values, as well as clashes and conflicts of artistic traditions and poetics.
Keywords: primerjalna literarna veda; Srednja Evropa; Central Europe; srednjeevropska književnost; multietničnost; multikulturnost